Deficits 10-Years after Achilles Tendon Repair - Horstmann, T.; Lukas, C.; Merk, J.; Brauner, T.; Mündermann, A. (International Journal of Sports Medicine, 2012)
The purpose of this study was to determine the long-term impact of surgical repair and subsequent 6-week immobilization of an Achilles tendon rupture on muscle strength, muscle strength endurance and muscle activity. 63 patients participated in this study on average 10.8±3.4 years after surgically repaired Achilles tendon rupture and short-term immobilization. Clinical function was assessed and muscle strength, strength endurance and muscle activity were measured using a dynamometer and electromyography. Ankle ROM, heel height during heel-raise tests and calf circumference were smaller on the injured than on the contralateral side. Ankle torques during the concentric dorsiflexion tasks at 60°/sec and 180°/sec and ankle torques during the eccentric plantarflexion task and during the concentric plantarflexion task at 60°/sec for the injured leg were significantly lower than those for the contralateral leg. The total work during a plantarflexion exercise at 180°/sec was 14.9% lower in the injured compared to the contralateral leg (p<0.001). Muscle activity for the gastrocnemius muscle during dorsiflexion tasks was significantly higher in the injured than in the contralateral limb. Limited ankle joint ROM and increased muscle activity in the injured leg suggest compensatory mechanisms to account for differences in muscle morphology and physiology caused by the injury.
Keywords: muscle strength; muscle strength endurance; muscle activity; Achilles tendon rupture